Interpretation the Concept of Transparency in the Strategic and Legislative Documents of Major Intergovernmental Organizations - Hohmann, Balázs (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2021)
Administrative procedures, as well as public bodies that carry out these procedures, ought to perform functions related to the application of administrative law in a constantly changing social, economic, and political environment. This presents them with new challenges and expectations time and time again. According to the findings of the this study, the relation of transparency and administrative procedures – which could be described as a type of historically rooted but, at the same time, contemporary expectation towards public administration – fits in the above concept. The study attempts to interpret and define the concept of transparency on the basis of the terminology used by international organisations in the field of the examination of administrative procedures, and thus to highlight the issues, divergences and their causes.